Commiphora myrrha extract protects pigeons from Eimeria labbeana-like-triggered inflammatory dysregulation - Abdel-Gaber, Rewaida; Albasyouni, Shurug; Santourlidis, Simeon; Al Quraishy, Saleh; Al-Shaebi, Esam (Frontiers in Immunology, 2025)
BackgroundCoccidiosis, caused by Eimeria species, is a major enteric disease in birds, with Eimeria labbeana-like isolates frequently inducing severe intestinal lesions, diarrhea, and reduced weight gain in pigeons. Conventional anticoccidial drugs face limitations due to resistance, residue concerns, and environmental impact, highlighting the need for alternative strategies. Commiphora myrrha (myrrh) is a resinous plant extract rich in bioactive compounds with antioxidant, antimicrobial, antiparasitic, and anti-inflammatory properties. This study evaluated the protective effects of C. myrrha resin in pigeons experimentally infected with E. labbeana-like isolates.MethodsResin of C. myrrha was collected from Riyadh, Saudi Arabia, authenticated, and extracted with 70% methanol to prepare a crude extract (MyE). Its chemical composition was characterized using GC–MS. A laboratory strain of Eimeria labbeana-like oocysts was propagated in pigeons, sporulated, and used for experimental infection. Twenty-five pigeons were randomly assigned to five groups: uninfected control, uninfected + myrrh extract (MyE), infected control, infected + MyE, and infected + amprolium (standard drug). MyE and amprolium treatments were administered orally for 5 days post-infection. Parasitological, histological, immunohistochemical (NF-κB and IFN-γ), gene expression (MUC2, IL-1β, IL-10, IFN-γ, and TNF-α), and cytokine (IL-10 and TNF-α) analyses were conducted.ResultsIn this study, myrrh resin was methanol-extracted and characterized by GC–MS, revealing 29 phytochemical components. Experimental infection of pigeons with E. labbeana-like oocysts resulted in peak fecal oocyst shedding (~5.25 × 105 oocysts/g.feces), extensive development of intracellular parasite stages (meronts, gamonts, and developing oocysts), a marked reduction in goblet cell numbers, and elevated intestinal inflammatory responses, including increased NF-κB and IFN-γ immunoreactivity, as well as upregulated mRNA expression of IL-1β, IL-10, IFN-γ, and TNF-α. Oral administration of MyE significantly suppressed oocyst shedding by 60%, reduced the number of intracellular parasitic stages, restored goblet cell counts, and downregulated both gene and protein levels of pro-inflammatory markers while enhancing MUC2 expression, indicating effective modulation of Eimeria-induced intestinal damage and inflammatory dysregulation.ConclusionThese findings demonstrate that C. myrrha extract effectively mitigates Eimeria-induced intestinal damage, inflammation, and immune dysregulation, highlighting its potential as a natural, plant-based intervention for managing pigeon coccidiosis.